2016
DOI: 10.2147/ijn.s116006
|View full text |Cite
|
Sign up to set email alerts
|

Alkaline nanoparticle coatings improve resin bonding of 10-methacryloyloxydecyldihydrogenphosphate-conditioned zirconia

Abstract: Creating an alkaline environment prior to 10-methacryloyloxydecyldihydrogenphosphate (MDP) conditioning improves the resin bonding of zirconia. The present study evaluated the effects of four alkaline coatings with different water solubilities and pH values on resin bonding of MDP-conditioned zirconia. Two alkaline nanoparticle coatings were studied in particular. Thermodynamics calculations were performed to evaluate the strengths of MDP-tetragonal phase zirconia chemical bonds at different pH values. Zirconi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 18 publications
(38 reference statements)
1
20
0
Order By: Relevance
“…The increase in hydroxyl groups provided by zirconium hydroxide contributed to the improved chemical affinity of MDP for zirconia. 35 These findings are consistent with previous studies, suggesting that bonding of MDP and zirconia is enhanced by zirconium hydroxide. 29 Our NMR analysis also showed that prior Zr(OH) 4 coating positively impacted MDP bonding with zirconia.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…The increase in hydroxyl groups provided by zirconium hydroxide contributed to the improved chemical affinity of MDP for zirconia. 35 These findings are consistent with previous studies, suggesting that bonding of MDP and zirconia is enhanced by zirconium hydroxide. 29 Our NMR analysis also showed that prior Zr(OH) 4 coating positively impacted MDP bonding with zirconia.…”
Section: Discussionsupporting
confidence: 93%
“…Our NMR and XPS analyses indicated that Zr(OH) 4 enhanced bonding of MDP to zirconia, which is consistent with previous findings. 35 Moreover, previous experiments have shown that the addition of 10 wt% MDP-conditioned Zr(OH) 4 -coated zirconia does not significantly improve the flexural strength of resin composites. 22 In our study, we controlled the concentration of zirconium chloride used to avoid the influence of excess zirconium hydroxide on the properties of resin composites.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Pilo et al 22. and Qian et al 23. assessed the chemical bonding by Fourier transform infrared spectroscopy (FTIR).…”
mentioning
confidence: 99%